2023
DOI: 10.1111/cas.15988
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target cells of human papillomavirus 18 using squamocolumnar junction organoids

Yusuke Toyohara,
Ayumi Taguchi,
Yoshiyuki Ishii
et al.

Abstract: Human papillomavirus 18 (HPV18) is a highly malignant HPV genotype among high‐risk HPVs, characterized by the difficulty of detecting it in precancerous lesions and its high prevalence in adenocarcinomas. The cellular targets and molecular mechanisms underlying its infection remain unclear. In this study, we aimed to identify the cells targeted by HPV18 and elucidate the molecular mechanisms underlying HPV18 replication. Initially, we established a lentiviral vector (HPV18LCR‐GFP vector) containing the HPV18 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…At present, the main method for modeling CC organoids is to isolate tumor cells from CC tissue. In addition, some studies have also constructed organoids using the matrix gel method by using normal squamous columnar junction tissue from patients undergoing total hysterectomy ( Toyohara et al, 2023 ). In addition, studies have shown that culture media play an important role in constructing organoids of different tissue types ( Huang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, the main method for modeling CC organoids is to isolate tumor cells from CC tissue. In addition, some studies have also constructed organoids using the matrix gel method by using normal squamous columnar junction tissue from patients undergoing total hysterectomy ( Toyohara et al, 2023 ). In addition, studies have shown that culture media play an important role in constructing organoids of different tissue types ( Huang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Toyohara et al constructed CC organoids using the matrix gel method, transfected the lentiviral vector (HPV18LCR-GFP vector) into squamous columnar junction (SCJ) organoids from patients, and evaluated the presence of green fluorescence protein (GFP)-positive cells ( Toyohara et al, 2023 ). The results showed that pathways related to cell cycle and viral carcinogenesis were upregulated in GFP-positive cells, while keratinization and mitochondrial autophagy/autophagy-related pathways were upregulated in GFP-negative cells.…”
Section: Cervical Cancer (Cc) Organoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have focused on HPV18 target cells, carcinogenesis, and histological differentiation, suggesting that HPV18 may be characterized by latent infection and carcinogenesis in stem cell-like cells. 50,51 HPV generally changes the pattern of HPV gene expression in the differentiated cervical stratified squamous epithelium. E6/E7 is usually expressed in the basal layer, E1^E4, which is involved in interaction with the keratin network, is expressed in the differentiated layer, and L1, which is involved in capsid formation, is expressed in the surface epithelium.…”
Section: Human Papillomavirus18mentioning
confidence: 99%